Group Exhibition-We can never go back again, that much is certain. The past is still too close to us - Antoniou, Klitsa (My University, 2026)
We can never go back again, that much is certain. The past is still too close to us. An Art Intervention by the Fine Arts Department at Forest Park Hotel, Platres Cyprus.